Exemplar Parents' Practices of Engagement with Their Children's Learning in Finland and Portugal: A Multiple-Case Study. (10th February 2022) - Levinthal, Cristiana; Kuusisto, Elina; Tirri, Kirsi
Abstract : Parental engagement is a central aspect of children's holistic education, i.e., schooling-related and nonschooling-related learning. Parents' role in supporting such integrative learning is increasingly necessary to develop students' social, emotional, and intellectual skills. Nonetheless, it remains unclear which parental practices support holistic learning. The purpose of this qualitative multiple-case study was to identify and describe the current practices of engagement with learning of four exemplar parents in Finland ( N = 2) and Portugal ( N = 2). These four parents of primary-school-age children were individually interviewed, and abductive content analysis was performed to analyze their narratives. Our results evidence four patterns of exemplar practices: showing active interest in the child, supporting autonomy, building a partnership with the teacher and the school, and visiting the child's school. The study concludes that even though exemplar parents use a variety of specific engagement practices, they support holistic learning through their ownership of action in such interactions, clear awareness about their parental role, and consistency in their intentions. Exemplar parental engagement within different cultural contexts was discussed. Recommendations for teachers' pedagogy are presented regarding the benefits of digital communication, goal-oriented invitations to school, and promotion of family time in the home for enhancing children's holistic learning.